Legal Protection for Unrecorded Waqf: An Analytical Study at the Kuala Tungkal Religious Court - Ahmad Farhan Subhi; Hasbi Umar; Fuad Rahman (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Unregistered Waqf is still a common problem in West Tanjung Jabung Regency, which can cause legal disputes and hinder the optimization of waqf benefits for the community. Many waqf assets are only declared verbally or through private deeds without official registration by applicable legal provisions. Therefore, this study aims to analyze legal protection for unregistered Waqf through the Waqf isbat mechanism at the Kuala Tungkal Religious Court and the role of judges in determining waqf isbat through legal ijtihad. This study uses a normative juridical method with a statute and conceptual approach. Research data were obtained through observation, interviews with judges at the Kuala Tungkal Religious Court, and studies of relevant documents. The results of the study indicate that waqf isbat is an effective legal instrument in providing legal protection for unregistered Waqf because court decisions can be the basis for nazhir to make official registrations at the Indonesian Waqf Agency (BWI) and the National Land Agency (BPN). Judges in deciding waqf isbat cases are not only guided by applicable regulations but also carry out legal ijtihad by considering maqashid al-shariah to ensure the benefit of Waqf and its legal certainty. However, there are obstacles in the implementation of waqf isbat, such as long administrative procedures and lack of coordination between related institutions, so it is necessary to simplify procedures and harmonize regulations to increase the effectiveness of waqf isbat in protecting unrecorded waqf assets. Thus, waqf isbat can be a more optimal legal solution in guaranteeing the legal status and sustainability of waqf benefits for Muslims in Indonesia.